The Important Role of Environmental Justice in Supporting Green Schools - Aminah Zuhriyah (Ilomata International Journal of Social Science, 2023)
The world's awareness of the importance of protecting the earth's environment is proof that nature is seen as an inseparable part of humankind. For this reason, the application of green schools is increasingly being carried out as evidence of the achievement of Education for Sustainable Development (ESD). This research is related to the success of Al-Fajar Bekasi Islamic High School in implementing environmental justice in supporting green schools. This research method uses a qualitative phenomenological approach. The research findings show that the environmental justice approach plays a full role in supporting the creation of green schools for the long term. Student behavior that is in accordance with environmental justice, namely equality between humans will support that nature is an important component. Thus, the urgency of a pro-environmental attitude combined with adaptation to environmental justice for sustainable development must be instilled from an early age in public and private schools, so that later the younger generation will become the group that determines the success of environmental development in Indonesia with optimal and credible knowledge, attitudes and skills.